Widespread Rift Valley Fever Emergence in Senegal in 2013–2014. (21st July 2016) - Sow, Abdourahmane; Faye, Ousmane; Ba, Yamar; Diallo, Diawo; Fall, Gamou; Faye, Oumar; Bob, Ndeye Sakha; Loucoubar, Cheikh; Richard, Vincent; Dia, Anta Tal; Diallo, Mawlouth; Malvy, Denis; et al.
Abstract: Rift Valley fever (RVF), which caused epizootics and epidemics among human and livestock populations, occurred in Senegal in 2013–2014. A multidisciplinary field investigation was carried out in 3 regions of Senegal. We found 11 confirmed human cases of Rift Valley fever, including severe cases with encephalitis and retinitis, 1 pool of mosquito ( Aedes ochraceus ), and 52 animals tested positive for the disease. Symptoms such as encephalitis and macular retinitis were the most severe cases reported so far in Senegal. The outbreak was widespread due to animals' movements, leading to the largest RVF outbreak in Senegal in terms of geographic spreading and reaching areas that never reported RVF activity previously.